Venous thromboembolism and its prophylaxis in elective total hip arthroplasty: an international perspective. - Chari, A; Khokhar, A; Murray, D; McNally, M; Pandit, H (2012)
INTRODUCTION: Patients undergoing total hip arthroplasty (THA) are at high risk of developing post-operative deep vein thrombosis (DVT) or a subsequent pulmonary embolus (PE). Despite best efforts, the best prophylaxis for thromboembolic disease remains controversial. This article aims to update the reader on the newest guidelines concerning venous thromboembolism (VTE) prophylaxis for elective THAs, considering their advantages and disadvantages and highlighting their inconsistencies. METHODS: The Medline database and the Internet were searched for VTE prophylaxis guidelines in English. Nine guidelines were found and compared. The comparison looked at the recommendations made, the grade of recommendation, the level of evidence available for these recommendations and any inconsistencies between the guidelines. RESULTS: All guidelines advocate the use of LMWH and almost all advocate the use of mechanical methods of prophylaxis. The recommended duration ranges from 7-35 days and in many cases, the duration is not specified. There is little consensus in terms of other recommended drugs, the doses, duration and their recommendation grades. CONCLUSION: There is still uncertainty about the optimal methods of thromboprophylaxis in elective total hip arthroplasty. Although there are always going to be disagreements about the endpoints amongst guideline makers, guidelines should achieve uniformity in their criteria for levels of evidence and recommendation grades, facilitating the clinician's decision-making process.